Short selling regulation after the financial crisis – First principles revisited - Grünewald, Seraina N; Wagner, Alexander F; Weber, Rolf H (International journal of disclosure and governance, 2010)
This article examines the recent regulatory developments with regard to short selling. Short selling regulation is an important factor in firm governance because it affects the way in which firms are subject to market discipline. As the financial crisis has attracted regulators’ notice to short selling once again, it is important to understand the fundamental legal and economic arguments regarding short selling. These arguments have at their core the question of whether there exists a market failure. The available evidence on balance suggests that short selling restrictions hamper the price discovery process. Also, while regulations against market abuse are required, it is often an ineffective detour to pursue the goal of fair markets through the regulation of short selling. On the basis of these arguments, the article evaluates the approaches taken by the US and UK regulators, who play a leading part in the current movement towards more comprehensive short selling regulation. The US Securities and Exchange Commission's (SEC's) recently adopted rules do not seem to bring much added value and will presumably affect market efficiency in the negative. First principles suggest a somewhat more positive stance on the SEC's proposal for a circuit breaker rule and the UK. Financial Services Authority's proposed disclosure approach, though both are subject to caveats. We also highlight some central questions for future research.